“To give them free passage everywhere without opening or stopping”: Books for the Religious Communities of New Spain - García, Idalia (Cuadernos de Historia Moderna, 2017)
The acquisition of books for the libraries of religious communities in New Spain, remains a subject almost unknown. All evidence shows that such communities followed the same procedures required of booksellers and merchants. Among these, the presentation of one list of book and a review of the boxes, at the beginning and end of the journey. Such testimonies show us the formation of richand varied bibliographic collections and other related activities like the sale of books, both those produced under the patronage of religious orders and duplicate books in their libraries. In this text we intend to contribute to our knowledge about the acquisition of books in the Spanish America, through some preserved documents.
Keywords: Book trade; Convents; Religious libraries; Convent libraries; New Spain